Structure Of Mangrove Communities In Baturapa Village, Lolak District, Bolaang Mongondow Regency - Frian Patra; Ridwan Lasabuda; Adnan S. Wantasen (Sam Ratulangi University, 2021)
The Baturapa Village community uses mangroves to fulfill their various needs (fuel wood, house construction materials, color dyes and synthetic flower-making raw materials). This utilization must be carried out in a controlled manner to preserve the sustainability of the mangrove ecosystem. This study aims to determine the extent and the current structure of the mangrove community in Baturapa Village. The research was conducted in the mangrove area of Baturapa Village, Lolak District, Bolaang Mongondow Regency, North Sulawesi Province in March 2019.The method used was the line transect method to see the mangrove community structure including density, frequency, species dominance and Important Value Index (INP) and diversity index (H’). Mangrove area was calculated using Google earth pro and ArcGis 10.4 software. The outcomes of the calculation of the area of mangrove in the village of Baturapa are 37.4 hectares. The results of the identification of mangroves in the coastal area of Baturapa Village, Lolak District, Bolaang Mongondow Regency, have 11 species, with 111 total individuals. Of the 3 line transects, the highest species density is Rhizophora stylosa, 800 trees / ha (line transect III) with relative density ( KR) 57.1%, while T he highest frequency of species is Rhizophora stylosa with a value of 1.0 with a relative frequency (FR) of 50% (line transect III). The highest species dominance is Rhizophora mucronata with a value of 4.6 where relative dominance (DR) is 53.4% (line transect II). Furthermore, the highest species value index (INP) is Rhizophora stylosa with a value of 118.6 (line transect III). Line transect I has the highest diversity index (H;) with a value of 1.99. A value of 1.99 (H’) greater than 1 and smaller 3.3 means that productivity is sufficient, ecosystem conditions are quite balanced and ecological pressure is moderate.Keywords: Baturapa Village, mangrove area, density, frequency, dominance, index important value, mangrove diversity indexABSTRAKMasyarakat Desa Baturapa memanfaatan mangrove untuk memenuhi berbagai kebutuhan hidupnya (kayu bakar, bahan pembangunan rumah,pewarna jarin dan bahan baku pembuatan bunga sintetis). Pemanfaatan ini harus dilakukan secara terkendali untuk menjaga keberlanjutan ekosistem mangrove. Penelitian ini bertujuan untuk mengetahui luasan dan struktur komunitas mangrove saat ini di Desa Baturapa. Penelitian ini dilakukan di kawasan mangrove Desa Baturapa, Kecamatan Lolak, Kabupaten Bolaang Mongondow, Provinsi Sulawesi Utara pada bulan maret 2019. Metode yang digunakan yaitu metode line transect untuk mengetahui struktur komunitas mangrove meliputi kerapatan, frekuensi, domimasi spesies serta Indeks Nilai Penting (INP) dan Indeks keaneragaman (H’). Menghitung luas mangrove menggunakan sofware Google earth pro dan ArcGis 10,4. Hasil perhitungan luas mangrove di desa Baturapa 37,4 Hektar. Hasil identifikasi mangrove di wilayah pesisir Desa Baturapa Kecamatan Lolak Kabupaten Bolaang Mongondow terdapat 11 spesies, dengan total individu sebanyak 111. Dari ke-3 line transect, kerapatan spesies tertinggi dimiliki Rhizophora stylosa, 800 pohon/ha (line transect III) dengan kerapatan relatif (KR) 57,1 %. Frekuensi spesies tertinggi adalah Rhizophora stylosa dengan nilai 1,0 dengan frekuensi relatif (FR) 50% (line transect III). Dominasi spesies tertinggi adalah Rhizophora mucronata dengan nilai 4,6 dimana dominasi relatif (DR) 53,4% (line transect II). Selanjutnya Indeks Nilai Penting (INP) spesies paling tinggi yaitu Rhizophora stylosa dengan nilai 118,6 (line transect III). Line transect I memiliki indeks keanekaragaman (H’) tertinggi dengan nilai 1,99. Nilai 1,99 (H’) lebih besar 1 dan lebih kecil 3,3 ini berarti produktivitas cukup, kondisi ekosistem cukup seimbang dan tekanan ekologi sedang. Kata kunci : Desa Baturapa, luas mangrove, kerapatan, frekuensi, dominasi, Indeks nilai penting,Indeks keaneragaman mangrove